Organizational capacity and entrepreneurial behavior. Issue 4 (24th February 2020) - Svensson, Per G.; Andersson, Fredrik O.; Faulk, Lewis
Abstract: In this research note, we examine the relationship between organizational capacity and entrepreneurial behavior in a global sample of 165 nonprofit organizations operating in a single, rapidly growing field of nonprofit activity. Our findings show a strong relationship between organizations' entrepreneurial behavior and levels of organizational capacity. We discuss our results relative to the importance of both organizational capacity and entrepreneurial behavior in a rapidly growing nonprofit subsector. The results contribute to the continued development and refinement of theoretical and empirical work on the causal links between organizational capacity and entrepreneurial behavior more generally.